2013
DOI: 10.3109/14767058.2013.766691
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary myo-inositol supplementation in pregnancy on the incidence of maternal gestational diabetes mellitus and fetal outcomes: a randomized controlled trial

Abstract: Myo-inositol supplementation in pregnancy reduced the incidence of GDM in women at high risk of this disorder. The reduction in incidence of GDM in the treatment arm was accompanied by improved outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
2
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(114 citation statements)
references
References 14 publications
5
101
2
6
Order By: Relevance
“…Also Matarrelli et al found similar results conducting a prospective, randomized, double-blinded, placebo-controlled clinical trial [19]. They enrolled 84 non-obese singleton pregnant women with an elevated fasting glucose in the first or early second trimester randomizing them to receive either MI or placebo.…”
Section: Inositol As a Therapeutic Option To Prevent Gdmsupporting
confidence: 48%
See 1 more Smart Citation
“…Also Matarrelli et al found similar results conducting a prospective, randomized, double-blinded, placebo-controlled clinical trial [19]. They enrolled 84 non-obese singleton pregnant women with an elevated fasting glucose in the first or early second trimester randomizing them to receive either MI or placebo.…”
Section: Inositol As a Therapeutic Option To Prevent Gdmsupporting
confidence: 48%
“…Considering the insulin-mimetic effect of inositol supplementation in several animal models of insulin resistance [12][13][14] and in women with polycystic ovary syndrome (PCOS) [15], it has been recently hypothesized and studied its positive on the GDM incidence [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…26 Özellikleri nedeni ile, inositol tedavisinin gestasyonel diabetes mellitus (GDM) için etkili bir tedavi olduğu dü-şünülmektedir. 27 MI tedavisinin ailede Tip 2 diyabet öyküsü olan gebelerde GDM başlangıcını azaltıp azaltmadığını değerlendiren çalışmada, gebeliğinin 1. trimesterinde olan bireyler iki farklı gruba ayrılmıştır. Birinci gruba (n=110) 2 g MI ve 200 µg FA verilirken ikinci gruba (n=110) plasebo ve yalnızca FA günde iki kez verilmiştir.…”
Section: Gestasyonel Di̇abetes Melli̇tusunclassified
“…24 Yapılan başka bir çalışmada MI alan grupta gestasyonel diyabet insidansının plasebo alan gruba göre daha düşük olduğu bulunmuştur (p=0,001). 27 MI'nın GDM'de insülin direnci ve duyarlılığı üzerinde etkisini araştıran çalışmada araştırma grubuna (n=24) günde 4 g MI ve 400 µg FA verilirken kontrol grubuna (n=45) yalnızca 400 µg FA verilmiştir. Araştırma sonunda MI+FA alan grupta açlık kan glukozu, insülin düzeyi ve insülin direncinin diğer gruba göre daha düşük olduğu bulunmuştur.…”
Section: Gestasyonel Di̇abetes Melli̇tusunclassified
“…Megállapították, hogy mio-inozitol alkalmazásával az anyáknál csökkent az inzulinigény, és az anyák későbbi terhességi hétben szültek. A született magzatok adatait elemezve azt észlelték, hogy a készít-mény alkalmazásakor az újszülötteknél a macrosomia, valamint a születés utáni hypoglykaemia ritkább volt [23].…”
Section: Táblázatunclassified